Encyclopedia of Walt Disney’s animated characters - Grant, John (Hyperion, 1993)
From Mickey Mouse to Timon, Roger Rabbit to Hades, and Aladdin to Sebastian--the famous, the infamous, and the obscure--every character of the Disney honor roll is present and accounted for in this comprehensive volume that every true Disney fan and animation enthusiast will treasure.